Kiprijono Lukausko „Pamokslų“ kalba - Zinkevičius, Zigmas (Baltistica, 2001)
THE LANGUAGE OF PAMOKSLAI (‘SERMONS’) BY KIPRIJONAS LUKAUSKASThe paper is devoted to the analysis of the language of Pamokslai (‘Sermons’) by Kiprijonas Lukauskas, which, it is claimed, draws upon three basic sources: (1) the author’s native Žemaitish dialect, (2) the East Aukštaitish dialect, and (3) the traditional written language of the period. The primary source of Pamokslai is considered to be the Žemaitish dialect and the author’s native spoken variety of this dialect is traceable to the area where the North Žemaitish dialect called ‘kretingiškiai’ was spoken. Thus the findings of the present study contradict the viewpoint that the data under discussion belong to the South Žemaitish dialect called ‘dūnininkai’. The language of Pamokslai has also been influenced by the ‘puntininkai’ variety of the East Aukštaitish dialect because Lukauskas was a parish priest in Troškūnai for ten years. No evidence has been found to relate the language of Pamokslai to the West Aukštaitish dialect, although the influence of the written form of the language in use at that time is clearly obvious.
Keywords: lietuvių kalba; senieji raštai; Lukauskas; Pamokslai